Therapeutic effects of Kangxian Yanshen formula on patients with chronic kidney disease stages 3–4: a retrospective cohort study - Chu, Aojiao; Wei, Wenqian; Liu, Ni; Zhang, Fan; Zhang, Xianwen; Li, Xueling; Zheng, Rong; Ma, Zhifang; Li, Yi; Rong, Shu; Zhong, Yifei (Frontiers in Medicine, 2024)
Background This study retrospectively evaluated the actual efficacy of Kangxian Yanshen Formula Chinese medicine on renal function-related indicators in chronic kidney disease (CKD) stage 3–4 patients. Methods In this retrospective cohort study, we collected 212 adult CKD patients with baseline estimated glomerular filtration rate (eGFR) of 15–60 ml/min/1.73 m2. All participants received usual care (i.e., Western medications), and participants in the exposure group (n = 109) were additionally prescribed Kangxian Yanshen Formula Chinese medicine. The primary outcome was an adjusted hazard risk and 95% confidence interval (95% CI) of a 30% decrease in eGFR at month 36 from baseline. Results In terms of eGFR, among participants treated with additional Kangxian Yanshen Formula, after adjusting for covariates, there was a 57.1% reduction in the risk of a 30% decline from baseline in eGFR among participants in the Kangxian Yanshen Formula group compared with the Western medicine group (adjusted hazard risk: 0.429; 95% CI 0.269–0.682). In addition, participants in the Kangxian Yanshen Formula group had a significantly higher change in eGFR from baseline to month 12 than those in the western medicine group (3.40 ± 11.62 versus −3.87 ± 8.39; between-group difference Δ5.61 [± 2.26 standard deviation] mL/min/1.73 m2; P = 0.014). Participants in both groups showed a decreasing trend in eGFR at months 24 and 36. Conclusion In patients with stage 3–4 CKD, Kangxian Yanshen Formula Chinese medicine therapy may help delay eGFR decline, but high-quality randomized controlled trials are needed to validate the results further.